1980
DOI: 10.1182/blood.v55.1.61.bloodjournal55161
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic oscillation of blood neutrophils in a patient with multiple myeloma

Abstract: A patient with multiple myeloma developed periodic blood neutropenia (periodicity of 15–25 days) after 3 yr of intermittent treatment with cytotoxic agents. Peaks of serum colony-stimulating activity (CSA) level coincided with valleys of blood neutrophils. Fraction of marrow neutrophils in the multiplicative pool was high during blood neutrophil valleys and low during neutrophil peaks. In contrast, the maturation storage pool exhibited the reverse pattern. An increased fraction of marrow neutrophilic cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The disorder is usually familial, sometimes with similar but less pronounced variations of the neutrophils in asymptomatic relatives of patients (Morley et al, 1967b). Occasionally, however, it may be associated with either an underlying hematologic neoplasm (Natelson, 1953;Chikkappa et al, 1980) or with other diseases (Reimann, 1948(Reimann, , 1963Morley et al, 1967a,b). Figure 31 shows the cyclic variation in the number of circulating neutrophils and the about opposite variation in the number of circulating monocytes as seen in a patient who as a child was studied extensively by Page and Good (1957) and who was seen at this medical center for the first time 13 years later at the age of 29.…”
Section: Infi-adian Rhythms In Healthy Subjects Notmentioning
confidence: 99%
See 1 more Smart Citation
“…The disorder is usually familial, sometimes with similar but less pronounced variations of the neutrophils in asymptomatic relatives of patients (Morley et al, 1967b). Occasionally, however, it may be associated with either an underlying hematologic neoplasm (Natelson, 1953;Chikkappa et al, 1980) or with other diseases (Reimann, 1948(Reimann, , 1963Morley et al, 1967a,b). Figure 31 shows the cyclic variation in the number of circulating neutrophils and the about opposite variation in the number of circulating monocytes as seen in a patient who as a child was studied extensively by Page and Good (1957) and who was seen at this medical center for the first time 13 years later at the age of 29.…”
Section: Infi-adian Rhythms In Healthy Subjects Notmentioning
confidence: 99%
“…Experimental production of cyclic granulopoiesis in the dog was accomplished by inducing mild marrow failure by damage to the stem-cell compartment by treatment with alkylating agents and has more recently been reported in a patient with multiple myeloma treated over a prolonged time span with cytotoxic agents (Chikkappa et al, 1980). Morley et al (1967a) described four cases of chronic granulocytic leukemia that showed high-amplitude oscillations in the number of circulating leukemic leukocytes in the peripheral blood.…”
Section: Infi-adian Rhythms In Healthy Subjects Notmentioning
confidence: 99%
“…Most cases are congenital and two thirds are considered non-familial or sporadic. Acquired cases can present at any age, rarely in association with other blood or im-mune disorders, or neoplasms [Chikkappa et al, 1980;Loughran and Hammond, 19861. The familial form of this disorder appears to be autosomal dominant (ADCH) [(MIM 162800) Online Mendelian Inheritance in Man (OMIM), 1994)l but large pedigree structures and multigenerational blood counts are usually not reported. Although a number of case series described clinical manifestations, most do not distinguish familial and non-familial cases, or pool data from both.…”
Section: Introductionmentioning
confidence: 99%